Factors associated with reluctancy to acquire COVID-19 vaccination: A cross-sectional study in Shiraz, Iran, 2022 - Maharlouei, Najmeh; Hosseinpour, Parisa; Erfani, Amirhossein; Shahriarirad, Reza; Raeisi Shahrakie, Hadi; Rezaianzadeh, Abbas; Bagheri Lankarani, Kamran (PloS one, 2022)
Vaccination is a crucial action that can end the COVID-19 pandemic and reduce its detrimental effect on public health. Despite the availability of various vaccines, this study was conducted to better understand the factors behind individuals refusing to get vaccinated. The current cross-sectional study was conducted with individuals above 18 years of age in Shiraz, Iran, who were eligible but refused to receive the COVID-19 vaccination. Demographic features and factors related to their hesitancy and willingness to participate in the vaccination program were recorded in a questionnaire. Out of 801 participants in the current study, 427 (53.3%) were men, with a mean age of 37.92 years (± 14.16). The findings revealed that 350 (43.7%) participants claimed the side effects of the vaccine outweigh the benefits as one reason for their reluctance toward COVID-19 vaccination, followed by the unknown efficacy of vaccines (40.4%) and a lack of trust in vaccine companies (32.8%). Ensuring the safety of the vaccine (43.7%) and verifying its effectiveness (34.5%) were the most prevalent factors behind participating in the vaccination program. Those who reported their socio-economic status as low were significantly reluctant toward vaccination because of a self-presumption of high immunity (p-value < 0.001), the unclear efficacy of vaccines (p-value < 0.001), the side effects outweighing the benefits of vaccines (p-value < 0.001), distrust of vaccine companies (p-value < 0.001), usage of mask, gloves, and sanitizers (p-value < 0.001), contradictory speech of health authorities regarding vaccines (p-value = 0.041), and the unavailability of trusted vaccines (p-value = 0.002). It should also be noted that participants reported a greater likelihood to obtain information about vaccination reluctance from family and friends (p-value <0.001) and complementary medicine professionals (p-value <0.001). Avoiding vaccination is an undeniable public and individual health concern in Iran, as demonstrated in the current study. Concern about vaccine efficacy and side effects is the most reported cause of vaccination reluctance among individuals, which could be altered by emphasizing mass education and averting an infodemic by forming dedicated multidisciplinary organizations.